Analisis Faktor yang Mempengaruhi Kepuasan Pembeli di Kopi Kenangan Menggunakan Metode Regresi Logistik Biner - Aditya Mohamad; Agus Setiyanto; Bangkit Widhi Raharjo; Jerry Heikal (Jurnal Syntax Admiration, 2024)
This study aims to analyze various factors that affect buyer satisfaction with Kopi Kenangan. The method used in this study is the binary logistic regression method using SPSS. The number of samples was 68 consumers who came directly to Kopi Kenangan, with the variables used being product, packaging, price, service quality, cleaness/comfort, waiting time, discount, and interior/exterior design. Sample collection was carried out through filling out a survey form filled out by 68 buyer consumers who came directly to Kopi Kenangan. The results of the survey are outlined in Microsoft Excel and then data normalization is carried out. For Independent Variable data in the form of Text will be converted to binary numbers which means it is represented by numbers between 0 to 1, while for Dependent Variables it will be converted to 0 and 1. Independent Variable data consists of product, packaging, price, services, cleanliness/ comfort, waiting time, discount, and interior/ exterior design. The Data Dependent Variable is Satisfactory. From the results of the study, it can be concluded that the factors that affect buyer satisfaction are the variables of product, discount, and interior/exterior design. The variables of packaging, price, services, cleanliness/comfort, and waiting time did not significantly affect buyer satisfaction at Kopi Kenangan. With data accuracy of 89.7%. From the results of the assessment of the equation above, it can be concluded that there are 59 consumers who have a Satisfactory value and 9 consumers who do not have a Satisfactory value.